A Survey of Text-to-Image Generative Adversarial Networks - Kulkarni, Siddhivinayak; Dhondse, Amol; Katakkar, Anurag; Bannur, Nitish; Deshpande, Trupti (International Journal of Computer Sciences and Engineering, 2025)
In recent years, generative models have gained alot of attention in the deep learning community. In particular,Generative Adversarial Networks (GANs), proposed by Ian Goodfellow et al. in 2014, and their variants have emerged as a powerful method which performs significantly better than other generative models such as Restricted Boltzmann Machines or Variational Auto-Encoders. In this paper, we focuson a specific type of GANs, the Text-to-Image GANs, and review some of the most seminal work which has been conducted in this area. We provide a high-level description of the architectural components of these models and also review their performance on variousdatasets. Further, we discuss how these architectures are suitedfor the particular use case of text-to-face image synthesis for generating images of human faces from text descriptions.